Aplication of prohexadione calcium in strawberry seedlings cv. Pircinque - Molano, Zulma Paola; Rufato, Leo; Miranda, Diego; Faguerazzi, Antonio Felippe (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
In Brazil, strawberry production is conditioned by the importation of seedlings from different countries, with variable levels of adaptation, different cold requirements and high costs of the introduced material. The national production of seedlings of good genetic, physiological and phytosanitary quality, constitutes a viable alternative for Brazilian producers dedicated to this productive activity. The objective of this work was to evaluate the effect of the application of different concentrations and times of application of calcium prohexadione (ProCa) (growth retardant in various cultivated species), on the magnitude changes of the propagation structures, growth and development of strawberry seedlings cv. Pircinque, the productive behavior and the quality of the fruit. The experiment was carried out in the Agricultural Sciences Center of the Santa Catarina State University (CAV-UDESC) in Lages / SC (Brazil), with a 5 x 2 factorial design, five concentrations of prohexadione calcium (0, 100, 200, 300 and 400 mg L-1) and two periods of aplication (20 and 30 days after the planting of the rooting stolon). In the seedlings, the following were evaluated: number of leaves, crown diameter, height seedling and leaf area. The parameters evaluated in the strawberry plants were: number of fruits per plant, average fruit weight, total fruit weight, dry weight of leaves and crowns, during the cycle 2019/2020. Additionally, firmness, total soluble solids (TSS), titratable. acidity (TA) and ratio were evaluated. The application of ProCa significantly reduces vegetative growth and induces an increase in physiological responses in 'Pircinque' strawberry seedlings, such as leaf area and height for both application periods. On the other hand, ProCa concentrations did not influence the number of fruits and the mass of fruits per plant, nor the quality parameters of the fruit, with the exception of firmness, where it was favored by the concentration of 400 mg L-1. The results were related to the application time factor, where at 20 DAT the highest values of the morphological variables of the seedlings and plants were presented and on the contrary, applications at 30 DAT decrease the number of commercial fruits per plant.